2010
DOI: 10.2151/jmsj.2010-313
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Tropical Cyclones in the Northern Indian Ocean Associated with Two Types of Tropical Intraseasonal Oscillation Modes

Abstract: Over the northern Indian Ocean (NIO), a substantial number (@ 60%) of tropical cyclones (TCs) form in association with significant intraseasonal oscillation (ISO) events (i.e., Nargis [2008]). In this paper the relationship between TC genesis and ISO in the NIO was studied using 30-year (1997-2008) observations. Because NIO TCs mainly occur in transitional seasons when climatological environmental forcing favors TC genesis, two types of ISO modes, boreal summer intraseasonal oscillation (BSISO) and Madden-Jul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 86 publications
6
102
0
Order By: Relevance
“…As will be shown, BSISO1 represents the canonical northward propagating BSISO over the ASM region addressed in many previous studies with a 30-60 day quasi-oscillating period (e.g., Annamalai and Sperber 2005;Wang et al 2005;Kikuchi et al 2012). BSISO2, on the other hand, mainly captures the northward and northwestward propagating BSISO with periods of both around 30 days and 10-20 days (e.g., Kikuchi and Wang 2010).…”
Section: Basic Characteristics Of the Bsiso Indicesmentioning
confidence: 94%
See 1 more Smart Citation
“…As will be shown, BSISO1 represents the canonical northward propagating BSISO over the ASM region addressed in many previous studies with a 30-60 day quasi-oscillating period (e.g., Annamalai and Sperber 2005;Wang et al 2005;Kikuchi et al 2012). BSISO2, on the other hand, mainly captures the northward and northwestward propagating BSISO with periods of both around 30 days and 10-20 days (e.g., Kikuchi and Wang 2010).…”
Section: Basic Characteristics Of the Bsiso Indicesmentioning
confidence: 94%
“…It is also a possible source of seasonal climate predictability for precipitation (Wang et al 2009a;Lee et al 2010) and extratropical atmospheric circulation (Ding and Wang 2005;Lee et al 2011;Wang et al 2012). Two different periodicities of the BSISO have been identified: periods of 30-60 days (e.g., Wang et al 2005) and 10-20 days (e.g., Kikuchi and Wang 2010). The wet and dry spells of the BSISO strongly influence extreme hydro-meteorological events, major driving forces of natural disasters, and thus the socio-economic activities in the World's most populous monsoon region (Lau and Waliser 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The temporal and horizontal resolutions of this dataset, which is available from 1979, are 6 h and 1.25 degree, respectively. The JRA-25 dataset has been widely used in investigating the environmental characteristics for the generation of TCs [8,[23][24][25][26]. There is also a study [27] which compared the representations of the environmental conditions for TCs in various reanalysis datasets and found that there are no pronounced differences among the datasets.…”
Section: Data and Analysis Proceduresmentioning
confidence: 99%
“…It is understood that the FNISO plays the critical role in triggering the southwest monsoon over the BoB and has unique structure different from boreal winter Madden-Julian Oscillation (MJO) and boreal summer intra-seasonal oscillation (BSISO) (Li et al 2013a). Even though there are some previous studies on the ISO's modulation on the BoB cyclones (Camargo et al 2009;Kikuchi and Wang 2010;Yanase et al 2012;Krishnamohan et al 2012), (2)…”
Section: Dominant Process Associated Fniso To Modulate the Ov Genesismentioning
confidence: 99%
“…This peculiar feature is attributed to the strong modulation by seasonal monsoon circulation (Gray 1968;Yanase et al 2012;Li et al 2013b). It is also identified that BoB TCs are strongly influenced by the intra-seasonal oscillation (ISO) (Camargo et al 2009;Kikuchi and Wang 2010;Yanase et al 2012;Krishnamohan et al 2012). Monsoon onset represents the critical time when the seasonal transition is realized by the intrusion of the first northward-propagating intra-seasonal oscillations (FNISOs) into the central BoB (Li et al 2013a).…”
Section: Introductionmentioning
confidence: 98%